Heavy metals uptake in closed-recirculating water system for phytoremediation : a study towards aquaponic as biosensor tool for environmental biotechnology - Edward Entalai, Besi (2014)
Closed-artificial aquaponic system enables us to study the accumulation of heavy metals by plant in real simulation of the ecosystem, without endangering the environment. Heavy metals accumulation in the environment poses great risks to flora and fauna. Phytoremediation is applied to purify the heavy metals in the environment by using plant. In this study, the concentrations of heavy metals (Cu, Pb, Ni, Zn) accumulated by the wheatgrass (I'riticum aestivum) are monitored by using Atomic absorption spectroscopy (AAS) and observing its effects to the plant. Triticum aestivum is suggested as a best candidate to be a accumulator plant for phytoremediation. Other than that, Triticum aestivum is also identified as a tolerant plant for phytostabilization. Plant can be used as the natural environmental biosensor by observing the changes in morphological characteristics of the Triticum aestivum after being exposed to the heavy metals. The percentage of phytotoxicity of Triticum aestivum, which depend on changes in length of shoots and roots of the Triticum aestivum, increases as the concentration of the heavy metals accumulated by the Triticum aestivum increases. The changes in anatomy of the plants due to the toxicity of the heavy metals are studied by using Scanning Electron Microscopy (SEM). Bioaccumulation Coefficient Factor (BCF) and Translocation Factor (TF) of heavy metals are studied to determine whether Triticum aestivum is a good candidate for accumulator plant and also tolerant plant in phytoremediation. Water quality measurement are monitored, and measured by using Portable Kit, to find the relationship between the conditions of the water and the level of metals toxicity and also the Bioaccumulation Factor (BCF) and Translocation Factor (TF) of the heavy metals. The effects of heavy metals to the biochemical properties of Triticum aestivum, such as content of chlorophyl (a and b), carotenoid, and flavonoid, are also being studied. Fishless cycling of aquaponic system is preferable to the study involving analysis of heavy metals, since the addition of heavy metals can lead to high mortality of the fish. Aquaponic is used as a biosensor tool to detect the presence of heavy metals in contaminated water for further research related to phytoremediation. Atomic absorption spectroscopy (AAS) methods are very suitable methods for monitoring the levels of heavy metals in natural water or plants. They provide accurate and rapid determinations. The data from the AAS analysis is analyzed based on graphs of concentrations against time. The energy source of an Atomic Absorption spectrometer will emits resonance line radiation. The AAS has more than one channel for simultaneous detection and determination of several elements. The absorbance of the heavy metals are directly proportional to the concentration of the heavy metals itself.